2020
DOI: 10.1177/2397198320942038
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension screening practices in scleroderma patients among Canadian rheumatologists

Abstract: Background: Current international guidelines recommend annual screening for pulmonary arterial hypertension with transthoracic echocardiogram and pulmonary function testing in all patients with scleroderma (systemic sclerosis). Our objectives were to determine Canadian rheumatologists’ screening practices for pulmonary arterial hypertension in patients with systemic sclerosis and identify reasons why current guideline recommendations may not be followed. Methods: A survey was emailed to all Canadian Rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As for the rheumatologists' knowledge concerning screening, half of the respondents identified unfamiliarity with the proposed algorithms as a barrier, which is higher than previously reported in rheumatologists surveyed in Ohio (USA) (33.0%) 34 or Canada (21.6%). 31 Interestingly, we found that one-third of respondents considered that screening requires invasive testing, which may reflect respondents incorrectly conflating or confusing diagnostic testing with screening.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…As for the rheumatologists' knowledge concerning screening, half of the respondents identified unfamiliarity with the proposed algorithms as a barrier, which is higher than previously reported in rheumatologists surveyed in Ohio (USA) (33.0%) 34 or Canada (21.6%). 31 Interestingly, we found that one-third of respondents considered that screening requires invasive testing, which may reflect respondents incorrectly conflating or confusing diagnostic testing with screening.…”
Section: Discussionmentioning
confidence: 81%
“…For example, the rate reported by Morrisroe et al 17 found 84.4% adherence to annual screening guidelines via the algorithm proposed by ASIG; however, the adherence rate to annual screening in non-ASIG rheumatologists was much lower (38.5%-58.9%). Quinn et al 31 found a somewhat lower screening rate (71.9%) for Canadian rheumatologists performing annual TTE and PFT. In contrast, Wigger et al 34 reported a much lower screening rate (58.0%) with both the same annual modalities (TTE and PFTs) in a specialised PH and SSc centre in Ohio, USA.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The main cause of death in SSc patients is not only collagen overproduction but also the effects collagen overproduction has on the pulmonary system. This includes fibrosis or pulmonary artery hypertension (PAH) [10][11][12][13][14][15]. Recent guidelines have recommend screening with high resolution computed tomography (HRCT) to diagnose interstitial lung diseases (ILD) in SSc patients at the baseline visit and once the diagnosis of ILD has been established [16,17], whilst a combination of HRCT and pulmonary function tests is recommended to quantify the extent and severity of ILD [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%